Concluding remarks [in 2019 Annual trends and outlook report] - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Njuki, Jemimah (International Food Policy Research Institute, 2019)
This report examines the ways in which explicit attention to gender is key to achieving the Malabo goals of shared prosperity and improved livelihoods through inclusive agricultural growth. The evidence presented here shows convincingly that gender gaps in assets, livelihood strategies, and control over income impose costs on households, communities, and nations. There have been attempts to estimate the costs of gender inequality in Africa south of the Sahara (SSA). For example, a report by UN Women estimates losses at an average of US$95 billion per year (UN Women et al. 2015). Although such estimates vary widely depending on their underlying assumptions, it is likely that, by focusing only on economic costs, they understate the full social costs of gender inequality in Africa. To identify pathways toward agricultural transformation, poverty reduction, and gender equality, this report applies the conceptual framework of the Gender, Agriculture, and Assets Project (GAAP) (Figure 14.1), which traces the gendered linkages between contexts, resources, livelihoods, and well-being. This framework helps us to better understand how policies and programs can help realize the Malabo commitment to gender equality.